Predictors of Job Satisfaction and Association with Psychological Distress Among Academic Medicine Faculty in Kazakhstan - Uristemova, Assem; Myssayev, Ayan; Meirmanov, Serik; Migina, Lyudmila (La Medicina del Lavoro, 2024)
Background: The growing concern for the faculty’s well-being is allied with the emotionally demanding nature of teaching, which has an adverse effect on physical and mental health. There is abundant evidence that academic medicine faculty are subjected to high rates of dissatisfaction, distress, burnout, and turnover among medical educators. This study is dedicated to the exploration of the association between job satisfaction and psychological distress among academic medicine faculty in Kazakhstan. Methods: The observational cross-sectional study was conducted among medical educators in Kazakhstan between 1 October and 25 December. The survey was completed by 715 representatives of academic medicine staff. The sample size was calculated by Epi Info Sample Size Calculator, version 7.0. Multinomial logistic regression analysis using the forced entry procedure was applied to identify the factors associated with job satisfaction. Results: The prevalence of job satisfaction, depression, anxiety, and stress was 19.2%, 40.6%, 41.3%, and 53%, respectively. Three variables were significantly associated with job satisfaction: having a partner (AOR=0.79; 95% CI 0.38-1.659), having work experience of 5-10 years (AOR=0.32; 95% CI 0.14-0.74), and holding a Ph.D. degree (AOR=0.40; 95% CI 0.18-0.91). Job satisfaction was significantly associated with depression (p=0.005) and stress (p